Changing Conceptions of the International Classroom and the Good Student? - Vinther, Jane; Slethaug, Gordon (HERMES - Journal of Language and Communication in Business, 2014)
The changing conception of international education and the instructors’ perception of the’ good student’ is the focus of this study. Differing teaching philosophies and pedagogies in diverse cultures mean different conceptions of the important qualities and appropriate behaviour of students. As the flow of migrating students increases globally, the classrooms become increasingly intercultural, students bring disparate competences and educational values with them, and traditional views on good teaching and good students are no longer ‘givens’. When international students fill classrooms in countries far from their own, they risk not having their abilities perceived as being as valuable as those of home students. In the Nordic and Anglophone countries, there is a wellestablished credo of the ‘good student’ as independent and self-motivated – a belief usually ascribed to Western philosophies and traditions hailing back to Humboldt and his ideas of autonomy, freedom, and critical thinking. By contrast, many Asian cultures purportedly honour and respect the instructor’s opinion and established knowledge above the student’s. This study investigates the attitudes of instructors in Canada and Denmark towards these cultural perceptions through the lens of changes in internationalisation over time and space. This study argues that, as a first step, instructors should become better grounded in and more explicit about their own traditions and cultural philosophies, so that they can build upon them for international teaching and learning. On the basis of responses from Canadian and Danish scholars, we aim to explore avenues towards a flexible, dynamic, and transnational conception of the good student.